New properties of carbon nanomaterials through zinc doping and application as a ratiometric fluorescence pH sensor. (October 2021) - Lu, Changfang; Chen, Dongxu; Duan, Yuanyuan; Zhang, Wei; Xie, Yue; Chen, Yinyin; Wang, Xianxiang
Graphical abstract: Zinc doping made the response of fluorescence intensity of carbon nanomaterials to pH-dependent, and Zn-doped carbon nanomaterials was coupled with ZnCdS quantum dots to form a ratiometric fluorescence pH sensor. Highlights: Zinc doping changed the response of fluorescence intensity of carbon nanomaterials to pH-dependent. The possible causes of the difference of optical properties were deduced through spectral analysis. A ratiometric fluorescence pH sensor based on Zn-doped carbon nanomaterials was fabricated. Abstract: Fluorescence intensity of carbon nanomaterials (CNMs) synthesized with ethanolamine hardly changed with pH value. Doping Zinc into CNMs improved optical properties of CNMs. On the one hand, the fluorescence quantum yield of CNMs increased, on the other hand, the fluorescence intensity of Zn-doped CNMs decreased with pH value. Coupling Zn-doped CNMs with ZnCdS quantum dots (QDs) as a dual emission system, the blue fluorescence intensity of CNMs (I450 ) decreased while the orange fluorescence intensity of QDs (I580 ) enhanced with pH value increasing. The ratio (I450 /I580 ) varied linearly with pH value in the range of 1–9 and correlation coefficient ( R 2 ) was 0.991. Furthermore, using the system as a ratiometric fluorescence pH sensor to determine ascorbic acid, a good linear relationship ( R 2 = 0.998) was found when the concentration of ascorbic acid ranged from 0–1600 μM and limit of detection (LOD) was as low as 0.082 μM.